Pemberian Beberapa Konsentrasi Pupuk Organik Cair Bio Sugih Dan Mulsa Organik Terhadap Pertumbuhan dan Produksi Tanaman Kacang Hijau (Phaseolus radiatus L.) - Rakhmat ' Fadli; Murniati ' '; Sri ' Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Green beans (Phaseolus radiatus L.) is a legume that has long been known and cultivated in Indonesia. Increased production and quality of green beans can not be separated from the technical cultivation is done, one of which is the provision of nutrients in the soil with organic fertilization and mulching. This study aims to determine the effect of combined administration of concentration liquid organic fertilizer and mulch Bio Sugih organikserta to get the best treatment on the growth and yield of green beans (Phaseolus radiatus.L). This study uses a completely randomized design consisting of two factors. The first factor is the concentration of liquid organic fertilizer bio sugih consists of 5 levels, the second factor was organic mulch comprises 3 levels, and consists of three replications. Data were analyzed statistically using analysis of variance and tested further by Duncan's multiple range test at 5% The results of analysis of variance showed that the combined administration of several concentrations of liquid organic fertilizer and bio sugih organic mulch does not affect the amount and ratio of primary branch canopy roots and influence on plant height, dry weight, flowering age, harvesting age, number of pods per plant, percentage pithy pods per plant, seed weight per plot and weight of 100 seeds. Based on the research granting bio fertilizer treatment combination sugih concentration of 1 cc / l of water and rice straw mulch resulted in seed weight per plot were higher than the other treatments. Keywords: green beans, sugih bio fertilizers and organic mulch.